2016
DOI: 10.1128/aem.00639-16
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Secretome Analyses of the Wood Decay Fungus Wolfiporia cocos Support Alternative Mechanisms of Lignocellulose Conversion

Abstract: Certain wood decay basidiomycetes, collectively referred to as brown rot fungi, rapidly depolymerize cellulose while leaving behind the bulk of cell wall lignin as a modified residue. The mechanism(s) employed is unclear, but considerable evidence implicates the involvement of diffusible oxidants generated via Fenton-like chemistry. Toward a better understanding of this process, we have examined the transcriptome and secretome of Wolfiporia cocos when cultivated on media containing glucose, purified crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 46 publications
4
54
1
Order By: Relevance
“…Numerous studies have demonstrated the impact of culture conditions on transcript and protein accumulation levels in wood decay fungi (29,(40)(41)(42), including comparisons of expression on defined media (e.g., glucose, maltose, or crystalline cellulose) versus wood as a carbon source (43)(44)(45)(46)(47). However, there have been relatively few side-by-side comparisons of gene expression on different wood species (43,(48)(49)(50)(51)(52)(53)(54)(55).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated the impact of culture conditions on transcript and protein accumulation levels in wood decay fungi (29,(40)(41)(42), including comparisons of expression on defined media (e.g., glucose, maltose, or crystalline cellulose) versus wood as a carbon source (43)(44)(45)(46)(47). However, there have been relatively few side-by-side comparisons of gene expression on different wood species (43,(48)(49)(50)(51)(52)(53)(54)(55).…”
mentioning
confidence: 99%
“…Several prior transcriptomic analyses concluded that wood decay fungi express similar sets of plant cell wall-degrading enzymes on both hardwood and softwood, although there may be disparities in the expression of individual genes on different substrates (43,49,50,52,55). For example, Vanden Wymelenberg et al (55) found that 47 genes in the model white rot fungus Phanerochaete chrysosporium were upregulated ÏŸ2-fold on aspen versus pine, including 13 genes encoding GHs, while in P. placenta, 164 genes showed differential expression on the two substrates (roughly equal numbers upregulated on each substrate).…”
mentioning
confidence: 99%
“…P. scopiformis DAOMC 229536 was obtained from the Canadian Collection of Fungal Cultures. Two-liter flasks containing 250 ml of basal salt media (22) were supplemented with 1.25 g of P. contorta wood ground in a Wiley-mill (30 mesh screen) as the sole carbon source. Cultures were inoculated with mycelium scraped from the surface of malt extract agar (2% w/w malt extract, 2% glucose w/w, 0.5% peptone, 1.5% agar) and placed on a rotary shaker (150 RPM).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, a more detailed view of compounds that the microbe senses and responds to (‘bioavailability’) could come from analysis of its transcriptome from growth on plant biomass feedstocks. Studies observing gene expression of either lignocellulosic fungi (Gaskell et al ., , ; Couturier et al ., ) or lignocellulosic bacteria (Raman et al ., ; VanFossen et al ., ) grown on plant biomass feedstocks and sugars have so far focused on extracellular enzymes. Novel and useful insights into the plant biomass matrix in question could be obtained, based not only on the differential transcription of genes encoding glycoside hydrolases, but also including ATP‐binding cassette (ABC) sugar transporters and key metabolic pathway enzymes.…”
Section: Introductionmentioning
confidence: 99%